Characteristic of Local Humoral Factors of Nonspecific Resistance in Children with Recurrent Respiratory Infections - Yu.V. Marushko; O.S. Movchan (Zaslavsky O.Yu., 2014)
In this paper we investigated the content of defensins-β1-3, lactoferrin, lysozyme, sIgA A in oropharyngeal secretion in children with recurrent respiratory infections (RRI), with RRI and chronic compensated tonsillitis or atopic dermatitis, studied the correlation between these factors and clinical-anamnestic data. The findings suggest the need for differentiated approach to the treatment of children, who often suffer from acute respiratory diseases .